Answer:
It is clear that the multiplication of two values in Eq A is done to get the LCM while same method is not applied for eq B .
Step-by-step explanation:
Given as :
The two statement are
A) The LCM of 5 , 13 = 65
Here The multiple of 5 = 1 × 5
And The multiple of 13 = 1 × 13
So, Applying prime factor method,
least common multiple = product of height power of all factors that occur in resolution
So, LCM = 1 × 5 × 1 × 13
i.e LCM = 65
<u>Again</u>
B) The LCM of 6 , 8 = 24
Here The multiple of 6 = 1 × 2 × 3
And The multiple of 8 = 1 × 2 × 2 × 2
i.e The multiple of 8 = 1 × 2³
So, Applying prime factor method,
least common multiple = product of height power of all factors that occur in resolution
So, LCM = 2³ × 3
i.e LCM = 24
Hence, It is clear that the multiplication of two values in Eq A is done to get the LCM while same method is not applied for eq B . Answer